2012
DOI: 10.1371/journal.pone.0046796
|View full text |Cite
|
Sign up to set email alerts
|

Can a One-Item Mood Scale Do the Trick? Predicting Relapse over 5.5-Years in Recurrent Depression

Abstract: BackgroundTo examine whether a simple Visual Analogue Mood Scale (VAMS) is able to predict time to relapse over 5.5-years.Methodology/Principal Findings187 remitted recurrently depressed out-patients were interviewed using the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I) and the 17-item Hamilton Depression rating scale (HAM-D) to verify remission status (HAM-D <10). All patients rated their current mood with the help of a Visual Analogue Mood Scale (VAMS) at baseline and at a follow-up as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 50 publications
(42 reference statements)
1
38
0
Order By: Relevance
“…The circumplex model is a common EMA mood measure and recent studies have suggested that single-item mood measures can provide predictive information on the development of depressive symptoms (eg, [19]). However, there certainly remains much to be learned with regard to the psychometric properties of single-item EMA measures in different populations and contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The circumplex model is a common EMA mood measure and recent studies have suggested that single-item mood measures can provide predictive information on the development of depressive symptoms (eg, [19]). However, there certainly remains much to be learned with regard to the psychometric properties of single-item EMA measures in different populations and contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Levels on both dimensions were tapped on a 5-point scale scored from -2 to 2 (low to high). Because recent studies suggest that single-item mood measures can provide predictive information on the development of depressive symptoms (eg, [19]), we also added a one-dimensional mood question, which asked participants to rate their current mood on a 10-point scale, with 1 as the negative and 10 as the positive pole.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the subjects' pre-strategy mood ratings had to have a value of at least 10 (out of 100) on a visual analog scale so that the pre-mood was intense enough for participants to regulate it. The choice of this comparatively low threshold was based on the argument that research on cognitive and affective reactivity has shown that pre-existing, subtle mood deterioration may initiate depressogenic information processing in depression-prone individuals that may in turn lead to a vicious cycle of further mood-deterioration and increased depressogenic cognitions (Lau, Segal, & Williams, 2004;Segal, Gemar, & Williams, 1999;Teasdale & Barnard, 1993;Van Rijsbergen, Bockting, Berking, Koeter, & Schene, 2012).…”
Section: Waiting Conditionmentioning
confidence: 99%
“…Evidently, there are factors possibly impacting treatment response. For the purpose of this study repeated measures were selected on the basis of relevant studies [42,45], and clinical insights. Thus, the set of questions have been tailored to the specific characteristics of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Mood will be measured using a validated single item measure [45]. For the purpose of this study we have altered the item 'At the moment I feel' to 'In the last week I felt' to make the timespan congruent to the other pre-session measures for possible predictors.…”
Section: Mood-measured Before Each Sessionmentioning
confidence: 99%